Una aproximación teórica a la planeación en las organizaciones (2017)
This article arises within the framework of the research project about employers’ behavior towards integration agreements; it is part of a study of planning in organizations; it complements the paper Exploring methods of planning in organizations, published in the Questionar magazine volume No. 4. Its objective is to reflect on the concept of planning through the models that have emerged as a theoretical tool that bases their exercise in pursuit of higher competitiveness. Methodologically, the work is based on an exhaustive documentary review and epistemological approach to the subject. The result shows that the concept of planning is dynamic, to foresee uncertainty and is valuable to face the competitiveness generated by the new markets that globalization brings.